Kinerja Tenaga Kerja Terhadap Waktu Pelaksanaan Proyek Pembangunan Jalan Tol Layang AP.Pettarani, Makassar - Juslam Tamba; Josefine E Latupeirissa; Lintje Tammu Tangdialla (Paulus Civil Engineering Journal, 2020)
The growth of construction work requires human resources as a determining factor both in terms of quality of work. Of course, the quality of work is highly dependent on the skills of the workforce, so that labor is a major factor in the implementation of a job in order to achieve maximum results. Productivity good workforce is very influential for the success rate of a quality construction project in accordance with the quality planned. The data analysis technique in this research is descriptive qualitative analysis. The data in this study are primary data and secondary data. Observation of workforce performance is carried out on pile cap work which consists of work items for fixing formwork and construction. Determination of the sample using the Slovin formula so that the number of samples taken is 9 pile caps. To find out the workforce performance is to look at their productivity. Observations are made directly by looking at the volume and number of workers every day until the job is completed. Where is said to perform well if the productivity index> 1. From the results of the calculation of data analysis, the work productivity index of the pile cap PAF1 = 1.59; PAF2 = 1.59; PAF3 = 1.59; PAF4 = 1.59; P34 = 1.57; P35 = 1.57; P36 = 1.57; P37 = 1.57; P39 = 1.57 and pile cap work of PAF1 = 1.51; PAF2 = 1.51; PAF3 = 1.51; PAF4 = 1.51; P34 = 1.27; P35 = 1.27; P36 = 1.29; P37 = 1.29; P39 = 1.29. This condition indicates that the productivity index of each pile cap work item is performing well.